Information Technology Investment and Banks’ Stock Performance: An External Investor's Perspective - Ari Christianti (Universitas Trunojoyo Madura, 2026)
Information Technology (IT) investment in banks could influence investor perceptions of the bank's future prospects. IT investment in banks is often associated with service innovation, operational efficiency, increased competitiveness, and expanded market share. This study aims to empirically test the effect of IT investment in banks on stock market performance using unbalanced panel data and Fixed Effect Model (FEM) analysis. Furthermore, the sample used in this study was commercial banks listed on the Indonesia Stock Exchange, with the study period 2012-2022. The results show that IT investment in banks has been proven to have a positive impact on stock market performance. Banks with higher technology involvement tend to have strong stock returns. These findings have implications for banks to invest in IT not only to improve operational efficiency and expand service access, but also as a strategy to improve market performance. Furthermore, IT investment in banks can be used as an indicator for capital market investors in assessing banks' future prospects.